2010
DOI: 10.1002/bem.20602
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of mitochondrial activity in mediating ELF‐EMF stimulatory effect on human sperm motility

Abstract: It has recently been reported that the exposure of human spermatozoa to an extremely low frequency (ELF) electromagnetic field (EMF) with a square waveform of 5 mT amplitude and frequency of 50 Hz improves sperm motility. The functional relationship between the energy metabolism and the enhancement of human sperm motility induced by ELF-EMF was investigated. Sperm exposure to ELF-EMF resulted in a progressive and significant increase of mitochondrial membrane potential and levels of ATP, ADP and NAD(+) that wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 37 publications
0
24
1
Order By: Relevance
“…These higher frequencies might be responsible for the motility-stimulating effect of the square wave. Understanding of the mechanisms of the regulation of sperm motility is limited, but motion naturally needs energy, and reported evidence indicates that mitochondrial oxidative phosphorylation has a key role in mediating the effect of 50-Hz square wave MF on sperm motility (Turner, 2006, Iorio et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…These higher frequencies might be responsible for the motility-stimulating effect of the square wave. Understanding of the mechanisms of the regulation of sperm motility is limited, but motion naturally needs energy, and reported evidence indicates that mitochondrial oxidative phosphorylation has a key role in mediating the effect of 50-Hz square wave MF on sperm motility (Turner, 2006, Iorio et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, optimizing the cryopreservation procedure to reduce the concentration of ROS can be efficient for the preservation of microtubules in sperm during the freeze‐thaw process. Recently, earlier studies reported the beneficial effects of the extremely low electromagnetic field (ELEF) on the cryopreservation process of the sperm . The ELEF affects the physicochemical properties of water including the inhibition of ice nucleation at the higher degrees of supercooling, the production of small ice crystals throughout the frozen product, and the prevention of the cell destruction .…”
Section: Introductionmentioning
confidence: 99%
“…In latest years, several studies have been performed to verify direct effects exerted by ELF-EMF on cell functions. Although results have been somewhat controversial, a variety of cell responses have been observed involving proliferation and differentiation [110], gene expression [1114], modulation of the membrane receptors functionality [1520], apoptosis [2123], alteration in ion homeostasis [1, 6, 13, 2426], and free radicals generation [25, 27–30]. …”
Section: Introductionmentioning
confidence: 99%